Deferred tax for tax planning in the Czech agricultural companies - Hana Bohušová; Patrik Svoboda; Lucie Semerádová (Agricultural Economics (AGRICECON), 2019)
The paper is aimed at the materiality of deferred tax in agricultural holdings and the development of a proposal for simplification of deferred tax reporting in agriculture. The analysis of materiality and the structure of deferred tax in agricultural holdings which are obliged to report deferred tax is researched. The dataset covers the financial statements of the agricultural holdings (joint stock companies) obliged to report deferred tax during the period 2011-2015. The dataset covers hand-collected 1 110 firm-years. Based on the results of the study, the category deferred tax was identified as a material category and has to be reported. We found that the most common title for deferred tax reporting is the difference between the tax base and the carrying amount of long-term assets. The comparison of return on assets and adjusted return on assets reflecting the elimination of the deferred taxes effect reveals that the effect of deferred tax reporting is not so high in the large agricultural holdings in the Czech Republic.